Utilization of Technology Media in Era 4.0 on Students’ Creativity in Elementary Schools - Sari, Ratna; Rizky, Wulan; Tresnawati, Nailah; Putri, Dian Permana (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
In the era of the Industrial Revolution 4.0, fostering creativity at the elementary level is essential for equipping students with the critical thinking and problem-solving skills needed to adapt to rapid technological change. This study explores how the use of technology-based media influences student creativity in elementary schools. Employing a qualitative descriptive approach, data were collected through classroom observations, semi-structured interviews with teachers and students, and documentation across five selected public elementary schools in Cirebon City, Indonesia. The research focuses on how digital tools, such as learning videos, Canva, PowerPoint, and Wordwall, are integrated into classroom instruction and how they affect students’ learning interest, active engagement, and satisfaction. The findings showed that technology-supported learning environments contribute positively to the development of four core indicators of creativity: fluency, flexibility, originality, and elaboration. Students demonstrated greater confidence in generating and expressing ideas, adapted learning strategies independently, and produced more detailed and original work using digital platforms. Teachers also observed higher motivation and participation levels during technology-enhanced lessons. These results underscore the importance of incorporating digital media into pedagogical design to foster creativity among young learners. In conclusion, integrating technology-based media into elementary education effectively fosters students’ creativity by enhancing their idea generation, adaptability, and originality, while simultaneously increasing their motivation and active participation in the learning process.